(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the clinical and paraclinical characteristics of patients with systemic Lupus erythematosus who are positive for anti-C1q antibodies. Subjects and methods: A cross-sectional descriptive study was conducted on 43 patients with systemic Lupus erythematosus diagnosed according to the SLICC 2012 criteria and complicated by lupus nephritis, who were treated at the Clinical Allergy and Immunology Center, Bach Mai Hospital from August 2024 to August 2025. Results: The prevalence of anti-C1q antibody positivity was 72.1%. The mean ages of patients in the C1q-positive and C1q-negative groups were 31.4 ± 12.4 and 32.0 ± 13.4 years, respectively. The age at onset of lupus nephritis was higher in the C1q-positive group (29.4 ± 13.8 years vs. 21.7 ± 9.6 years). Mean blood pressure was lower in the C1q-positive group (121.5/75.6 mmHg vs. 141/87.9 mmHg). Clinically, malar rash was observed in 71.0% of C1q-positive patients and 83.3% of C1q-negative patients. Pleural and/or pericardial effusion was more frequent in the C1q-positive group (29.0% and 32.3%) than in the C1q-negative group (16.7%). Paraclinically, the C1q-positive group had higher anti-dsDNA levels (135.4 ± 69.5 IU/mL vs. 68.9 ± 66.2 IU/mL) and lower complement C3 and C4 levels (0.52 ± 0.26 g/L and 0.077 ± 0.073 g/L) compared with the C1q-negative group (0.65 ± 0.32 g/L and 0.138 ± 0.068 g/L). The C1q-negative group showed higher levels of urea, creatinine, and cholesterol. Conclusion: Anti-C1q antibody positivity is highly prevalent in patients with lupus nephritis and is associated with markers of disease activity, such as elevated anti-dsDNA levels and reduced complement levels. Anti-C1q is a valuable immunological marker for assessing and monitoring disease activity in lupus nephritis.